1997
DOI: 10.1111/j.1746-1561.1997.tb03448.x
|View full text |Cite
|
Sign up to set email alerts
|

A State‐Based Immunization Campaign: The New Mexico Experience

Abstract: Hepatitis B prophylaxis in the form of immunization has become an increasingly effective protective measure across the United States. Various cohorts have been targeted and methodologies used by public health officials to attain optimal coverage of the population. New Mexico is in its third year of school-based hepatitis B immunization programs. New Mexico's approach to this issue is characterized by significant rates of participation (66% in middle schools and 56% in high schools), high vaccination series com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…Successful projects relied on combined efforts by federal, state, and local health departments; school employees; parents; private providers; managed care organizations; and administrative bodies. [13][14][15] Project costs were subsidized by health departments, the Centers for Disease Control and Prevention, schools, vaccine manufacturers, and other local sources. A review of 9 studies of vaccination programs in schools (8 for hepatitis B vaccination) revealed that vaccination-coverage rates increased a median of 58 percentage points.…”
Section: Experience With School-based Vaccination In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful projects relied on combined efforts by federal, state, and local health departments; school employees; parents; private providers; managed care organizations; and administrative bodies. [13][14][15] Project costs were subsidized by health departments, the Centers for Disease Control and Prevention, schools, vaccine manufacturers, and other local sources. A review of 9 studies of vaccination programs in schools (8 for hepatitis B vaccination) revealed that vaccination-coverage rates increased a median of 58 percentage points.…”
Section: Experience With School-based Vaccination In the United Statesmentioning
confidence: 99%
“…Partnership between public health nurses and school nurses was an important factor in the success of New Mexico's school-based hepatitis B vaccination program. 15 Other effective organizations with which to partner will vary but could include community development or after-school programs. Local immunization coalitions can offer schools…”
Section: Linkagesmentioning
confidence: 99%
“…These initiatives were used most notably in the mid-1990s when the Advisory Committee on Immunization Practices made a universal recommendation for hepatitis B vaccination among all adolescents [1]. Ultimately, schoolbased programs, in conjunction with school-entry mandates, helped adolescents achieve compliance with the Advisory Committee on Immunization Practices recommendation [2,3] and improved youth access to immunization services [4][5][6][7].…”
mentioning
confidence: 99%
“…Overall, this may be an important intervention strategy when developing influenza SLIPs in order to build trust with families; however, implementation and post-implementation surveys studies have found that individual incentives for either return of consent forms or vaccination do not affect MS students' vaccination behaviors. [22][23][24][25] Because all groups noted the improved convenience of the SLIP, it will require further investigation to determine if this might serve as a more significant incentive for the parents to return the forms.…”
Section: Discussionmentioning
confidence: 99%